2020
DOI: 10.1186/s12986-020-00532-1
|View full text |Cite
|
Sign up to set email alerts
|

The dysregulation of the hypothalamic–pituitary–adrenal axis in diet-induced prediabetic male Sprague Dawley rats

Abstract: Background Altered function of the hypothalamic–pituitary–adrenal (HPA) axis in type 2 diabetic patients, a condition preceded by pre-diabetes, has been shown to increase the risk of depression as well as cause downstream effects resulting in upregulation of gluconeogenesis and dyslipidemia. In addition, stress, either psychological from managing diabetes or lifestyle related, further activates the HPA axis causing an exaggerated stress response. This study investigated the activity of the HPA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 83 publications
3
36
0
Order By: Relevance
“…[6] The metabolic T2DM abnormalities cause mitochondrial superoxide overproduction in endothelial cells of both large and small vessels. [19] SCIENTIFIC COLLECTION «INTERCONF» | № 117 219 Yoga therapy as a complex intervention with various components improves glycaemic control, reduces the risk of T2DM complications, and impacts remarkably on the course of the disease. [20] Patients with T2DM who completed the yoga program were characterised by significantly lower HbA1c, fasting blood glucose, and stress level compared to the group with low adherence to yoga training.…”
Section: Main Bodymentioning
confidence: 99%
“…[6] The metabolic T2DM abnormalities cause mitochondrial superoxide overproduction in endothelial cells of both large and small vessels. [19] SCIENTIFIC COLLECTION «INTERCONF» | № 117 219 Yoga therapy as a complex intervention with various components improves glycaemic control, reduces the risk of T2DM complications, and impacts remarkably on the course of the disease. [20] Patients with T2DM who completed the yoga program were characterised by significantly lower HbA1c, fasting blood glucose, and stress level compared to the group with low adherence to yoga training.…”
Section: Main Bodymentioning
confidence: 99%
“…Mechanistically, this passes through altered secretion of ACTH from the pituitary gland, leading to altered GC levels [ 68 , 69 ]. In a series of particularly well designed experiments, Mosili et al demonstrated that as rats entered a prolonged pre-diabetic state baseline ACTH levels under non-stressful conditions dropped, but GC levels were significantly elevated [ 70 ]. The HPA axis negative feedback loop should, under normal conditions, bring down GC levels when ACTH levels are low [ 71 ] suggesting that the negative feedback is somehow impaired [ 68 ].…”
Section: The Physiological Response To External Psychosocial Stresmentioning
confidence: 99%
“…The HPA axis negative feedback loop should, under normal conditions, bring down GC levels when ACTH levels are low [ 71 ] suggesting that the negative feedback is somehow impaired [ 68 ]. Furthermore, when Mosili et al induced a chronic stress together with pre-diabetes, the rats were unable to mount a normal ACTH or GC response to subsequent acute stressor, further consolidating their observation of either impaired GC signalling or negative feedback [ 70 ]. Interestingly, diet would appear to affect the adrenal gland as increased GC secretion, adrenal cortical hyperplasia, and increased steroidogenesis have been reported in T2D- and obesity-inducing high fat diets [ 72 ].…”
Section: The Physiological Response To External Psychosocial Stresmentioning
confidence: 99%
“…Previous studies in our laboratory developed a high fat high carbohydrate (HFHC) diet-induced pre-diabetic animal model which mimics the human condition of pre-diabetes ( 9 , 10 ). Several studies using this model have revealed that various complications seen in T2DM begin in the pre-diabetic state ( 9 , 11 ). While the changes to the functioning of calcium-regulating organs have been well documented in the diabetic state, these changes have not yet been investigated during the pre-diabetic state ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%